A Phase 1 Study to Investigate the Effects of Cortexolone 17α‐Propionate, Also Known as Clascoterone, on the QT Interval Using the Meal Effect to Demonstrate ECG Assay Sensitivity. Issue 6 (3rd May 2021) - Täubel, Jörg; Mazzetti, Alessandro; Ferber, Georg; Burch, William; Fernandes, Sara; Patel, Avani; Spencer, Christopher S.; Freier, Anne; Graff, Claus; Kanters, Jørgen K.; Camm, John
Abstract: Cortexolone 17α‐propionate, also known as clascoterone, is a potent androgen receptor inhibitor intended for the topical treatment of skin diseases associated with androgenic pathway alterations. In nonclinical studies, cortexolone 17α‐propionate was found to have a weak inhibitory effect on human Ether‐à‐go‐go‐Related Gene (hERG) potassium channels, which are vital for normal electrical activity in the heart. When used in a cream formulation, little cortexolone 17α‐propionate is absorbed. However, the solution formulation developed for the treatment of androgenetic alopecia leads to a measurable systemic concentration and accumulation of the antiandrogen. This phase 1 study assessed the effect of cortexolone 17α‐propionate on the QTc interval using concentration‐effect analysis and the effect of a meal on QTc to confirm assay sensitivity. Thirty‐two volunteers were randomly assigned to receive the active drug or a matching vehicle as placebo. Participants were dosed twice daily on days 1 to 3 (225 mg applied topically as a 7.5% solution 12 hours apart) and once on day 4. Pharmacokinetic and electrocardiogram assessments were performed after supratherapeutic doses. Assay sensitivity was successfully confirmed by using the food effect on the QTc interval. The results of this concentration‐QTc analysis demonstrate that cortexolone 17α‐propionate and its metabolite/degradation product had no effect on the QTc interval in the concentration range tested.